Homocysteine can aggravate depressive like behaviors in a middle cerebral artery occlusion/reperfusion rat model: a possible role for NMDARs-mediated synaptic alterations. (3rd June 2023) - Wang, Mengying; Liang, Xiaoshan; Zhang, Qiang; Luo, Suhui; Liu, Huan; Wang, Xuan; Sai, Na; Zhang, Xumei
ABSTRACT: Background: Post-stroke depression (PSD), the most frequent psychiatric complication following stroke, could have a negative impact on the recuperation of stroke patients. Hyperhomocysteinemia (HHCY) has been reported to be a modifiable risk factor of stroke. Objective: The study tries to explore the effect of HHCY on PSD and the role of N-methyl-d-aspartate receptors (NMDARs)-mediated synaptic alterations. Methods: Forty-five adult male Sprague–Dawley rats were randomly allocated into five groups: sham operation group, middle cerebral artery occlusion group (MCAO), HCY-treated MCAO group HCY and MK-801 co-treated MCAO group and MK-801-treated MCAO group. 1.6 mg/kg/d D, L-HCY was administered by tail vein injection for 28 d prior to SHAM or MCAO operationand up to 14 d after surgery. The MK-801 (3 mg/kg) was administered by intraperitoneal injection 15 min prior to MCAO operation. Results: HCY treatment aggravated depressive-like disorders of post-stroke rats by the open field test and sucrose preference test. Further, HCY significantly decreased central monoamines levels in the MCAO rats by HPLC. The transmission electron microscopy results showed that the number of synapses and the area of postsynaptic density decreased in the hippocampus of the HCY-treated MCAO rats. Additionally, HCY augmented ischemia-induced up-regulation of NMDARs, decreased the levels of synaptic structure-related marker PSD-95and the synaptic transmission-associated synaptic proteins (VGLUT1, SNAP-25 and Complexin Ι/ΙΙ). These effects of HCY were partly reversed by the NMDA antagonist MK-801. Conclusions: The current study suggested that NMDARs-mediated synaptic plasticity may be involved in the adverse effect of HCY on PSD.